Antimicrobial natural product research: A review from a South African perspective for the years 2009–2016. (17th August 2017) - Van Vuuren, S.; Holl, D.
Abstract: Ethnopharmacological relevance: This review provides information on the antimicrobial research which has taken place on South African natural products for the last eight years (2009–2016). This important field is the backbone of all studies involving the use of medicinal plants against infectious diseases and hence can form the mainstay for future studies. Materials and methods: All publications within the years 2009–2016 were considered. Exclusion criteria were studies not involving South African medicinal natural products and those publications where full articles could not be accessed. An overview of the most common experimental methods used and new advances in terms of antimicrobial investigations are provided. Disease categories selected for further investigation were skin and wounds, respiratory, gastrointestinal, sexually transmitted and ophthalmic infections amongst others. Alternate natural products and combinations studies were also included. Results: The minimum inhibitory concentration (MIC) was the most commonly used experimental method to determine antimicrobial activity. Staphylococcus aureus was the most commonly tested skin pathogen and Klebsiella pneumoniae was the most common pathogen implicated in respiratory disorders. Only 20% of gastrointestinal studies included commonly implicated pathogens such as Shigella flexneri and Campylobacter species. Conclusion: Multidisciplinary studies have emerged as a strong support for antimicrobial investigations and show the importance of including toxicity when studying antimicrobial efficacy. Alternate approaches (for example biofilms and quorum sensing) at examining antimicrobial effects are encouraged. Studies on resistant strains require more insight and future recommendations should look at consistent dosing and investigations on compound interactions amongst others. Graphical abstract: